PERAN PEREMPUAN DALAM JARINGAN TERORISME ISIS DI INDONESIA - Musfia, Nesa Wilda; Utomo, Tri Cahyo; Wahyudi, Fendy Eko (Journal of International Relations, 2017)
Womenâ€™s role in terrorist groups has been widely discussed by scholars (Agara, 2015; Yasefi, 2014; Martin. 2014; Nurhayati, 2015; Ratri, 2011; Magrfur & muniroh, 2013). Especially, in the emergence of ISIS which increases a long list of womenâ€™s role in terror cases. This study aims to explain womenâ€™s role in ISIS terrorism networks in Indonesia and the reasons that triggered the women to be involved. This research was done by using qualitative research method with descriptive research type. This research was analyzed by using social identity theory, psychological terrorism theory, and â€œwani ing tataâ€ concept as a cultural philosophy of Javanese culture. These theories were used in this research as theoretical frameworks. The result of this study shows that the roles that women have in the terrorist group were as important as those of menâ€™s. ISIS has a different strategy in involving women compared to other terrorist groups. In ISIS, women are motivated to involve by individual psychology/psychological condition, their closest relatives, as well as personal experiences along with their social identity as muslims.